CITRA MEREK TUJUAN WISATA DAN PERILAKU WISATAWAN: YOGYAKARTA SEBAGAI DAERAH TUJUAN WISATA - Roostika, Ratna - (JURNAL MANAJEMEN DAN AKUNTANSI, 2012)
Abstract: Brand is known as a valuable asset as it enables to differentiate from competitors offerings as well as to generate positive perceptions in the consumers’ mind. In the tourism sector, it is suggested that destination should also be branded. The objective of this study is to empirically examine how visitors recognize the slogan of “Jogja Never Ending Asia” when they visit Yogyakarta for leisure and examine the relationship whether brand destination image does has influence on visitors behavioural intentions. By applying purposive sampling, 144 valid questionnaires were analysed using linier regression and qualitative approach in interpreting visitors’ perception on their exposure to the slogan. Results indicate that there were positive influences between destination brand image to behavioural intentions, whereas majority of respondents did not semed to be familiar with Yogyakarta tourism slogan. This should call for higher commitment among all stakeholders of tourism in Yogyakarta in order to have Yogyakarta as having a well known positive image for tourism destination. Key words: Brand destination image, behavioural intentions, destination slogan.